Augmenting retail reality. part b, - Verma, Balraj; Mittal, Amit; Raman, Murali; Sindhav, Birud (Emerald Publishing Limited, 2024)
In the ever-evolving realm of retail commerce, the confluence of groundbreaking technologies is not merely a trend but a transformative force reshaping the industry's very foundations. 'Augmenting Retail Reality, Part B: Blockchain, AR, VR, and AI' delves into this dynamic landscape, offering an insightful exploration of how cutting-edge innovations are revolutionizing the retail experience. This book is designed to serve as a comprehensive guide for retailers, researchers, students, and technology enthusiasts, illuminating the path toward a future where technology and retail seamlessly intersect. As the retail sector undergoes rapid metamorphosis, driven by technological advancements, there is a critical need for a resource that comprehensively dissects the symbiotic relationship between technology and commerce. This book addresses that need by providing an in-depth analysis of technologies such as the Internet of Things (IoT), blockchain, Artificial Intelligence (AI), robotics, Augmented Reality (AR), and Virtual Reality (VR). Each chapter meticulously examines how these innovations are not only enhancing customer experiences but also driving operational efficiencies and unlocking new business opportunities.
Includes index.
Keywords: Chain stores.; Internet of things -- Economic aspects.; Augmented reality -- Economic aspects.; Computers -- Electronic Commerce.; Online marketing, Social media marketing.; E-commerce: business aspects.; elektronické knihy; electronic books